Studia Wstępne z Dziedziny Skręcania Kadłuba Okrętu na Fali Skośnej - Klott, Jerzy; Naleszkiewicz, Jarosław; Rutecki, Jerzy; Wituszyński, Kazimierz (Engineering Transactions, 1955)
To begin with, the problem of torsion with axial constraints of a bar of simplified cross-section is considered, the principal characteristics concerning the connectivity of cross-section being the same as for the hull of the real ship. These simplified cross-sections are shown in Figs. 1 to 14. Quantities characterizing these cross-sections for torsion with axial constraints and obtained on the basis of the «engineer’s» theory are represented. Next, the equation of torsion with axial constraints is derived according to the same theory. The form of the equation obtained is similar to that of the equation of torsion of a beam with open cross-section. In the next section the torsion of a cylindrical hull of a bark, composed of 5 segments of different cross-sections: closed doubly connected, open, simply connected (due to a hatchway), closed triply connected (the bridge-house being in the middle portion of the hull), closed-open doubly connected (with hatchway and double bottom) and finally, closed triply connected (with a double bottom). The example is characterized by the lack of diaphragms. The formulas of torsion of different portions of the hull are simple to derive on the basis of the results of the foregoing section, but a new difficulty is encountered in the necessity of choosing the boundary conditions in such a way a that the deformations be continuous in the planes where the cross-section changes. To overcome this difficulty equalizing self-equilibrating stress systems are introduced in each segment of the hull. Finally, equations for the parameters of the self-equilibrating systems are derived. In the last section the method of substitute space lattices is used for the determination of approximate values of stresses in the skin and the corners of the hatchways. Two extreme cases are considered: (1) the diaphragms may be considered to be perfectly flexible in their planes, (2) they are assumed absolutely rigid. In the first case the hull becomes a statically determinate lattice, in the second a statically indeterminate lattice of a special type (i.e. the most simple from the point of view of computation). The values obtained for these cases determine the limits of all stresses in the hull which is an interesting complement of the computations of the preceding section. Some elementary methods of approximate strength computations of cylindrical vessels for torsion caused by an oblique wave are explained. These may constitute starting points for further improvements of approximate methods of strength computation in hulls of ships. Each of the discussed approximate methods is applied to the same numerical example thus illustrating the features of each method.